FAKTOR STRATEGIS RUMAH POTONG UNGGAS DINAS PETERNAKAN DAN KESEHATAN HEWAN KABUPATEN MERAUKE - Anthonia Karolina Rejo Lobwaer (Universitas Musamus,Merauke,Papua, 2019)
Regulations reduce deviant behavior towards food processing. The Poultry Slaughterhouse of the Livestock and Animal Health Services carries out various mandate of the regulation. Knowing the RPU's strategic factors as well as strategic alternatives is the aim of this research. Research uses the Analytical Strategy Formulation technique. It was found that the strategic strength lies in the ability to access information and regulation, facilities and funding. The strategic weakness lies in the management that has not been maximized both in terms of organization namely the UPTD, HR and the lack of promotion and outreach. Market availability, regulation and technology of farmers that continue to increase provide opportunities instead of distribution, cuts that deviate from regulations, and changes are strategic factors that pose a threat. HR becomes the most attractive strategic alternative that is expected to drive the performance of the RPU.